Goat Milk Foodomics. Dietary Supplementation of Sunflower Oil and Rapeseed Oil Modify Milk Amino Acid and Organic Acid Profiles in Dairy Goats - Vargas-Bello-Pérez, Einar; Khushvakov, Jaloliddin; Ye, Yongxin; Pedersen, Nanna Camilla; Hansen, Hanne Helene; Ahrné, Lilia; Khakimov, Bekzod (Frontiers in Veterinary Science, 2022)
Dietary supplementation of vegetable oils is known to improve dietary energy density as well as milk fatty acid profile, however, impacts on milk metabolome is largely unknown. This study investigated the effect of two different sources of unsaturated fatty acids, rapeseed oil or sunflower oil, as a feeding supplement on the milk foodome from dairy goats. Nine Danish Landrace goats at 42 ± 5 days in milk were allocated to three treatment groups for 42 days with three animals per group. A control group received a basal diet made of forage and concentrate at 85:15 ratio. On top of the basal diet, the second and third groups received rapeseed oil or sunflower oil supplements at 4% of dry matter, respectively. Goat milk was sampled on day 14, 21 and 42. Milk foodome was measured using gas chromatography-mass spectrometry and proton nuclear magnetic resonance spectroscopy. Milk levels of 2-hydroxyisovaleric acid, oxaloacetic acid, and taurine were higher in milk from goats fed with sunflower oil compared to the control group. More glucose-1-phosphate was found in milk from goats fed with rapeseed oil compared to the control group. Amino acids, valine and tyrosine, and 2-hydroxyisovaleric acid and oxaloacetic acid were higher in sunflower group compared to the rapeseed group, while the milk from the rapeseed fed goats had greater levels of ethanol and 2-oxoglutaric acid compared to the sunflower group. Thus, results show that foodomics is suitable for studying how milk chemistry changes as a function of feeding regime.